Estimating species richness with camera traps: modeling the effects of delay period, deployment length, number of sites, and interference imagery. (17th September 2022) - Mashintonio, Andrew F.; Harris, Grant M.; Stewart, David R.; Butler, Matthew J.; Sanderson, Jim; Russell, Gareth
Abstract: Biologists commonly use camera traps for estimating species richness to inform conservation actions, steer land protection, and reveal effects of climate change. Long‐term studies using short delay periods (≤1 min) and numerous cameras produce voluminous amounts of redundant imagery. Thus, camera‐trapping procedures maximizing richness estimates while minimizing data collection need development. We used imagery of mammals spanning 4 deserts in the United States to model the effects of delay, deployment length (i.e., study duration), number of sampling sites, and interference events on the proportion of known species richness detected ( R p ). We also determined the proportion of subsamples containing each species (SR) under different sampling conditions to inform subsequent occupancy estimation. We generated contour plots describing the optimal configuration of sites and deployment length that minimized the image acquisition required to estimate R p = 0.9. The optimal configuration was independent of delay (requiring 50 sites and 13 months). The shortest delay (10 sec) generated 8 times more images than the longest (3600 sec) without substantially improving R p and rare species detection. The shortest duration to acquire R p = 0.9 was 10 months but required 70 sites. The fewest sites needed were 22 and 29, depending on camera placement, requiring approximately 50 months of deployment. Simulated short, one‐month studies were only able to obtain R p 0.6 with 40–70 sites. Obtaining SR = 0.8 with a 3600 sec delay required between 1–12 months and 10 sites or 1–17 sites and 6 months for uncommon species. Adding interference imagery, even with long delays, produced SR ≥ 0.5 for rare species, generating data suitable for occupancy estimation. Overall, interference imagery had minimal effects on reducing SR estimates, unless the interference occurred continuously. Our guidance optimizes the number of sites, deployment length, and delay period while minimizing imagery acquisition to meet R p and occupancy objectives with confidence. Abstract : Our study shows that increasing camera trap delay period has little to no effect on estimates of species richness, depending on other factors such as the number of study sites or length of camera deployment. Practitioners can use these results to minimize excessive image collection, reducing the time and cost for analysis.